Analisis Kualitas Pelayanan Dengan Metode Importance Performance Analysis (IPA) Studi Kasus Pada Gubug Makan Mang Engking Lembang - Alif Choirun Nisa; Asni Mustika Rani; Muhardi (UNISBA Press, 2023)
Gubug Makan Mang Engking Lembang is a company engaged in the food & beverage sector. So far, Gubug Makan Mang Engking Lembang has never measured service quality, so it is not yet known how far the current consumer satisfaction is. Judging from the consumer complaint data, it shows that 61% of visitors complained about service, 22% of visitors complained about cleanliness, and 17% of visitors complained about food. Therefore the researchers wanted to analyze the quality of service at the Mang Engking Lembang Eating Shack by going directly to the field and using the IPA method. Based on the results of the gap calculation, it shows that visitors to Gubug Makan Mang Engking Lembang not all indicators experience satisfaction with what visitors expect, especially the competence dimension. From the results of the IPA calculation which is divided into 4 quadrants, namely in quadrant I (Top Priority) there are 3 indicators whose services must be considered by the company, quadrant II (Maintain Achievement) there are 7 indicators whose service performance must be maintained, quadrant III (Low Priority) there are 7 indicators whose services have a low priority for the company, quadrant IV (Excessive) there are 3 indicators whose services have good performance but are not of the main interest for the company.